Impaired olfactory performance and anxiety-like behavior in a rat model of multiple sclerosis are associated with enhanced adenosine signaling in the olfactory bulb via A1R, A2BR, and A3R - Stekic, Andjela; Dragic, Milorad; Stanojevic, Jelena; Zaric Kontic, Marina; Stevanovic, Ivana; Zeljkovic Jovanovic, Milica; Mihajlovic, Katarina; Nedeljkovic, Nadezda (Frontiers in Cellular Neuroscience, 2024)
The present study shows that animals with experimental autoimmune encephalomyelitis (EAE) exhibit olfactory dysfunction and impaired general cognitive abilities as well as anxiety-like behavior. Olfactory dysfunction occurs on average at 2 dpi, well before the onset of the first motor signs of EAE (8-10 dpi). After the initial olfactory dysfunction, the EAE animals show a fluctuation in olfactory performance that resembles the relapsing-remitting course of human MS. The study also shows severe neuroinflammation in the olfactory bulb (OB), with numerous infiltrated CD4 + T cells and peripheral macrophages in the superficial OB layers, marked microgliosis and massive induction of TNF-α, IL-1β and IL-6. Reduced tyrosine hydroxylase activity in the glomerular layer, pronounced granule cell atrophy and reduced numbers of type B neuroblasts in the rostral migratory stream also indicate altered plasticity of the neuronal network in the OB. Considering the exceptionally high purinome expression in the OB, the possible involvement of purinergic signaling was also investigated. The study shows that macrophages infiltrating the OB overexpress A 3 R, while highly reactive microglia overexpress the adenosine-producing enzyme eN/CD73 as well as A 2B R, A 3 R and P2X4R. Given the simultaneous induction of complement component C3, the results suggest that the microglial cells develop a functional phenotype of phagocytizing microglia. The study also demonstrates transcriptional and translational upregulation of A 1 R in mitral and tufted cells, which likely influence resting network activity in OB and likely contribute to olfactory dysfunction in EAE. Overall, our study shows that olfactory dysfunction and altered social and cognitive behavior in EAE are associated with increased adenosine signaling via A 1 R, A 2B R and A 3 R.